2006
DOI: 10.1111/j.1365-2672.2006.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

The microbial degradation of azimsulfuron and its effect on the soil bacterial community

Abstract: Aims:  Azimsulfuron is a recently introduced sulfonylurea herbicide useful in controlling weeds in paddy fields. To date very little information is available on the biodegradation of this pesticide and on its effect on the soil microbial community. The aim of this work was to study its biodegradation both in slurry soil microcosms and in batch tests with mixed and pure cultures. Methods and Results:  Azimsulfuron was applied to forest bulk soil in order to study its effect on the structure of the bacterial soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…In the last decade more than 20 different products of sulfonylurea herbicides have been commercialized for the worldwide application and other active compounds are under investigation (Valle et al 2006). Until now there are some reports about the influences of sulfonylurea herbicides on soil microorganisms (microbial biomass, soil respiration, soil enzymes activity, and nitrogen and carbon metabolism) by conventional culture methods (Gigliotti et al 1998;Yamamoto et al 1998;El-Ghamry et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade more than 20 different products of sulfonylurea herbicides have been commercialized for the worldwide application and other active compounds are under investigation (Valle et al 2006). Until now there are some reports about the influences of sulfonylurea herbicides on soil microorganisms (microbial biomass, soil respiration, soil enzymes activity, and nitrogen and carbon metabolism) by conventional culture methods (Gigliotti et al 1998;Yamamoto et al 1998;El-Ghamry et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although DGGE was used to study the impact of pesticides and some sulfonylurea herbicides on soil communities (Johnsen et al 2001;Valle et al 2006), until now it has been rarely used to study the effect of bensulfuronmethyl (Saeki and Toyota 2004). In this work, application of BSM affected the diversity of the soil microbial community structure from week 1 to week 3; whereas, the effects of BSM was mitigated at the end of the experiment (week 5) where no obvious different bands were observed in the banding profile of a DGGE gel (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DGGE is an established method for examining the impact of herbicide exposure in soils (Seghers et al, 2003;de Lipthay et al, 2004;Saeki and Toyota, 2004;Seghers et al, 2005;Ros et al, 2006;Valle et al, 2006), few studies have used DGGE analysis to examine the impact of herbicides on aquatic microorganisms. Our data revealed that exposure to acetochlor decreased bacterial community complexity, as the fingerprints collectively representing water samples exposed to 1, 5, 50 and 100 mg acetochlor l À1 contained significantly fewer bands relative to those representing the control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-denaturing gradient gel electrophoresis (DGGE) and PCR-temperature gradient gel electrophoresis (TGGE) are among the most established methods for molecular community profiling 27) . Until now, the impacts of various pollutants on microbial communities in environmental samples have been studied by PCR-DGGE/TGGE, and many studies indicated changes in the community or dominance of certain members following pollution 8,23,32,37) . Such observations are helpful to find key members involved in the degradation of pollutants under environmental conditions.…”
mentioning
confidence: 99%